Review Of Senior Nursing Students' Performance On GCS Assessment Of Head Injury Patient - Mardiana, Mansor; Fitriyatun, Mohamed; Lim, Chin Choon (2016)
A review was conducted on senior nursing students performing Glasgow coma score (GCS) assessments on head injury patients. This review addressed the scenario of management for students weak in performing Glasgow coma score on head injury patient and is based on management theory to overcome this problem. There are various articles that generally presented the challenges of nursing students in practical area while assessing head injury patient using Glasgow coma score. This article reviews on factors that contributed towards this disease and the scenario faced by senior nursing students weak in performing Glasgow coma score. Theoretical framework and Models are discussed in this article as a guideline based on management perspectives. Furthermore, a review on corrective action to solve the weakness of senior nursing students in performing Glasgow coma score on head injury patients was conducted. By using current model, lecturer and clinical instructor may develop skills among senior nursing students to excel in practical settings especially on the GCS. The use of management based models in teaching at clinical setting is important to produce nursing students with excellent skills that is related to quality care of patients in hospitals.